The mixture volume sprayed by hydraulic and centrifugal energy nozzles for the control of Asian soybean rust - Costa, Lilian Lucia [UNESP] (2015)
The objective of this work was to evaluate a means of controlling ASR (Phakopsora pachyrhizi H. Sydow & P. Sydow) by applying reduced fungicide volumes in association with spray nozzles using either hydraulic or centrifugal energy. Two experiments resulted from that objective: soybean plants (Glycine max (L.) Merril) of the 'BRS Valiosa RR' cultivar were grown at the Experimental Farm of the University of Sao Paulo State (Unesp) in Jaboticabal, Brazil. The treatments were distributed in the field according to a randomized complete block design with four replications. The treatments consisted of the volumes of 50, 100, and 150 L ha(-1) (droplets resulting from hydraulic energy) and 17, 35, and 50 L ha(-1) (droplets resulting from centrifugal energy). An additional treatment was applied without fungicide (i.e., baseline treatment). The volume of 150 L ha(-1) with droplets formed by hydraulic energy permitted the best pathogen control using the fungicide azoxystrobina and cyproconazole in comparison with the other treatments. The volume of 17 L ha(-1) with the droplets formed by centrifugal energy was the least efficient and resulted in the highest rust severity and the lowest grain yield.